Antimicrobial Efficacy of Cardamom and Star Anise Powders on E. coli O157:H7 and other Microbial Quality Indicators in Minced Beef under Refrigeration Storage (5±1oC) - Kumar, A. Vinoth; Pal, U. K.; Mandal, P. K.; Kasthuri , S.; Antony, P. X. (Journal of Meat Science, 2018)
Now-a-days consumers prefer natural foods without chemical preservatives. In this context, the present study was undertaken to evaluate  antimicrobial efficacy of cardamom and star anise powders against E. coli O157:H7 and other common microbial indicators in minced  beef during refrigeration storage (5±1oC). Reduction in E. coli O157:H7 population in 2 percent star anise powder treated samples was  significantly (P
Keywords: Antimicrobial activity; Cardamom powder; E. coli O157:H7; Minced beef; Star anise powder